Nucleotide variability and linkage disequilibrium patterns in the porcine MUC4 gene - Yang Ming; Yang Bin; Yan Xueming; Ouyang Jing; Zeng Weihong; Ai Huashui; Ren Jun; Huang Lusheng (BMC Genetics, 2012)
Abstract Background MUC4 is a type of membrane anchored glycoprotein and serves as the major constituent of mucus that covers epithelial surfaces of many tissues such as trachea, colon and cervix. MUC4 plays important roles in the lubrication and protection of the surface epithelium, cell proliferation and differentiation, immune response, cell adhesion and cancer development. To gain insights into the evolution of the porcine MUC4 gene, we surveyed the nucleotide variability and linkage disequilibrium (LD) within this gene in Chinese indigenous breeds and Western commercial breeds. Results A total of 53 SNPs covering the MUC4 gene were genotyped on 5 wild boars and 307 domestic pigs representing 11 Chinese breeds and 3 Western breeds. The nucleotide variability, haplotype phylogeny and LD extent of MUC4 were analyzed in these breeds. Both Chinese and Western breeds had considerable nucleotide diversity at the MUC4 locus. Western pig breeds like Duroc and Large White have comparable nucleotide diversity as many of Chinese breeds, thus artificial selection for lean pork production have not reduced the genetic variability of MUC4 in Western commercial breeds. Haplotype phylogeny analyses indicated that MUC4 had evolved divergently in Chinese and Western pigs. The dendrogram of genetic differentiation between breeds generally reflected demographic history and geographical distribution of these breeds. LD patterns were unexpectedly similar between Chinese and Western breeds, in which LD usually extended less than 20 kb. This is different from the presumed high LD extent (more than 100 kb) in Western commercial breeds. The significant positive Tajima’D, and Fu and Li’s D statistics in a few Chinese and Western breeds implied that MUC4 might undergo balancing selection in domestic breeds. Nevertheless, we cautioned that the significant statistics could be upward biased by SNP ascertainment process. Conclusions Chinese and Western breeds have similar nucleotide diversity but evolve divergently in the MUC4 region. Western breeds exhibited unusual low LD extent at the MUC4 locus, reflecting the complexity of nucleotide variability of pig genome. The finding suggests that high density (e.g. 1SNP/10 kb) markers are required to capture the underlying causal variants at such regions.